Improvement of Cooperative Spectrum Sensing in Rayleigh Fading and AWGN Environments for Cognitive Radio Networks - Haboub, Rayan Abdelazeem; Bilal, Khalid Hamid (Journal of engineering sciences and information technology, 2025)
Cognitive Radios (CRs) improve spectrum efficiency by tracking users' movements using spectrum-aware devices. However, inadequate spectrum sensing can cause interference and incorrect detection. This paper explores cooperative spectrum sensing using OR-rule's detection performance in AWGN and Rayleigh fading channels, revealing that cooperative spectrum sensing only slightly improves detection in low signal-to-noise ratio situations. The authors propose an adaptive threshold method for CRN receivers, which outperforms fixed threshold approaches and reduces sensing errors in low SNR situations, highlighting the effectiveness of adaptive thresholds in improving CRN sensing performance to improve detection efficiency. The study uses MATLAB to analyse the relationship between signal to noise ratio (SNR), detection probability, and false alarm probability. Results show that adaptive detection thresholds improve detection efficiency, especially in low SNR cases, addressing the issue of interference and enhancing detection accuracy.
Keywords: cognitive cycle; signal-to-noise ratio; Receiver Operating Characteristic; probability of false alarm; software-defined radio; cognitive radio